2016
DOI: 10.1038/srep39307
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Nutritional of Greenhouse Tomato in Response to Different Soil Aeration Volume at two depths of Subsurface drip irrigation

Abstract: This study investigated the effects of 4 aeration levels (varied by injection of air to the soil through subsurface irrigation lines) at two subsurface irrigation line depths (15 and 40 cm) on plant growth, yield and nutritional quality of greenhouse tomato. In all experiments, fruit number, width and length, yield, vitamin C, lycopene and sugar/acid ratio of tomato markedly increased in response to the aeration treatments. Vitamin C, lycopene, and sugar/acid ratio increased by 41%, 2%, and 43%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 47 publications
(58 reference statements)
3
32
0
1
Order By: Relevance
“…For the autumn-winter season in 2017, aeration had a slight and positive impact on tomato fruit quality, and the increasing rate of total soluble solids, lycopene, vitamin C, soluble sugar, organic acid, and sugar-acid ratio was 4.7%, 9.4%, 5.5%, 14.3%, 8.5%, and 6.8% than the control, respectively (Table 3), which was similar to previous results [6,37]. Moreover, high irrigation level decreased tomato fruit quality compared to low irrigation level, and the difference was significant for lycopene (p < 0.05, Table 3).…”
Section: Fruit Qualitysupporting
confidence: 90%
“…For the autumn-winter season in 2017, aeration had a slight and positive impact on tomato fruit quality, and the increasing rate of total soluble solids, lycopene, vitamin C, soluble sugar, organic acid, and sugar-acid ratio was 4.7%, 9.4%, 5.5%, 14.3%, 8.5%, and 6.8% than the control, respectively (Table 3), which was similar to previous results [6,37]. Moreover, high irrigation level decreased tomato fruit quality compared to low irrigation level, and the difference was significant for lycopene (p < 0.05, Table 3).…”
Section: Fruit Qualitysupporting
confidence: 90%
“…Upon harvesting, three fruits per treatment were sampled for measurements among the marked fruits. After weighing, the fruit sample was measured for longitudinal and transverse diameter (cm) using a Vernier calliper (Li et al ., ). The fruit shape index was analysed by longitudinal/transverse diameter.…”
Section: Methodsmentioning
confidence: 97%
“…Recent report on oxygenation irrigation experiments confirmed that using of oxygenated SDI water could increase crop yields, water use efficiency and salinity tolerance, the effect was more significant on heavy clay soils (Abuarab et al, 2013;Bhattarai et al, 2006Bhattarai et al, , 2008Ityel et al, 2014). Li et al (2016b) showed that soil aeration enhanced greenhouse tomato plant growth, yield fruit shape, and nutritional quality. Research on capsicum showed that increased oxygen concentration in the root zone by 5% by allowing roots to penetrate into the capillary barrier gravel layer and improved biomass and fruit yield by 16% and 18%, respectively (Ityel et al, 2014).…”
mentioning
confidence: 94%